Assessment of bacteriophage-encoded endolysin as a potent antimicrobial agent against antibiotic-resistant Salmonella Typhimurium. (July 2022) - Kim, Junhwan; Kim, Jin-Chul; Ahn, Juhee
Abstract: This study was designed to evaluate the potential of using newly purified Salmonella phage-encoded endolysin LysPB32 as novel antibiotic alternative. The endolysin LysPB32 was characterized by analyzing pH and thermal stability, lytic spectrum, antimicrobial activity, and mutant frequency against Salmonella Typhimurium KCCM 40253 (ST KCCM ), S . Typhimurium ATCC 19585 (ST ATCC ), S . Typhimurium CCARM 8009 (ST CCARM ), Klebsiella pneumoniae ATCC 23357 (KP ATCC ), K . pneumoniae CCARM 10237 (KP CCARM ), Pseudomonas aeruginosa ATCC 27853 (PA ATCC ), Listeria monocytogenes ATCC 1911 (LM ATCC ), Staphylococcus aureus ATCC 25923 (SA ATCC ), and S . aureus CCARM 3080 (SA CCARM ). The molecular weight of LysPB32 is 17 kDa that was classified as N -acetyl-β- d -muramidase. The optimum activity of LysPB32 against the outer membrane (OM) permeabilized ST KCCM, ST ATCC, and ST CCARM was observed at 37 °C and pH 6.5. LysPB32 had a broad spectrum of muralytic activity against antibiotic-sensitive ST KCCM (41 mOD/min), ST ATCC (32 mOD/min), and SB KACC (25 mOD/min) and antibiotic-resistant ST CCARM (35 mOD/min) and KP CCARM (31 mOD/min). The minimum inhibitory concentrations (MICs) of polymyxin B against ST KCCM, ST CCARM, and ST ATCC were decreased by 4-, 4-, and 8-folds, respectively, when treated with LysPB32. The combination of LysPB32 and polymyxin B effectively inhibited the growth of ST KCCM, ST CCARM, and ST ATCC after 24 h of incubation at 37 °C, showing 4.9-, 4.4-, and 3.3-log reductions, respectively. The mutant frequency was low in ST KCCM, ST CCARM, and ST ATCC treated with combination of LysPB32-polymyxin B system. The results suggest the LysPB32-polymyxin system can be a potential candidate for alternative therapeutic agent to control antibiotic-resistant pathogens. Highlights: The purified endolysin LysPB32 was stable at pHs ranging from 5 to 7 and temperatures between 25 and 37 °C. The muralytic activity of endolysin LysPB32 against Salmonella Typhimurium was enhance in the presence of polymyxin B. The combination of LysPB32 and polymyxin B was effective in controlling antibiotic-resistant Salmonella Typhimurium.